Psychological Adjustment And Its Relationship With Some Variables Among Married Minors In The Southern Region In Jordan (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to know the level of psychological adjustment of a sample of married underage girls, and the study also sought to reveal the impact of some variables such as age at marriage, and the age difference between spouses on the level of psychological adjustment. The study sample consisted of  (81) girls. To achieve the objectives of the study, the psychological adjustment scale was developed, which consists of (30) items that measure four basic areas: self conscious ,emotional balance, social maturity, and family stability. The study’s findings show that the level of psychological adjustment was at a low degree among the study sample members, and the results also revealed the absence of a statistically significant relationship in psychological adjustment due to the variable of age and age difference between spouses.  The study ended with a set of recommendations, such as the necessity of educating minors to better understand the nature of married life And the factors affecting them and the new variables and their reflection on their psychological compatibility and the need to realize sufficient knowledge about their future roles and challenges and how to overcome these challenges with high efficiency.